Recent advancement in Bi5O7I-based nanocomposites for high performance photocatalysts. (February 2022) - Hassan, Qadeer Ul; Channa, Ali Imran; Zhai, Quan-Guo; Zhu, Gangqiang; Gao, Yongxiang; Ali, Nisar; Bilal, Muhammad
Abstract: Bi5 O7 I belongs to the family of bismuth oxyhalides (BiOX, X = Cl, Br, I), having a unique layered structure with an internal electrostatic field that promotes the separation and transfer of photo-generated charge carriers. Interestingly, Bi5 O7 I exhibits higher thermal stability compared to its other BiOX member compounds and absorption spectrum extended to the visible region. Bi5 O7 I has demonstrated applications in diverse fields such as photocatalytic degradation of various organic pollutants, marine antifouling, etc. Unfortunately, owing to its wide band gap of ∼2.9 eV, its absorption lies mainly in the ultraviolet region, and a tiny portion of absorption lies in the visible region. Due to limited absorption, the photocatalytic performance of pure Bi5 O7 I is still facing challenges. In order to reduce the band gap and increase the light absorption capability of Bi5 O7 I, doping and formation of heterostructure strategies have been employed, which showed promising results in the photocatalytic performance. In addition, the plasmonic heterostructures of Bi5 O7 I were also developed to further boost the efficiency of Bi5 O7 I as a photocatalyst. Here, in this review article, we present such recent efforts made for the advanced development of Bi5 O7 I regarding its synthesis, properties and applications. The strategies for photocatalytic performance enhancement have been discussed in detail. Moreover, in the conclusion section, we have presented the current challenges and discussed possible prospective developments in this field. Graphical abstract: Image 1 Highlights: Recent progress in Bi5 O7 I-based nanocomposites for degradation of organic pollutants. Synthesis, properties, and photocatalytic applications of Bi5 O7 I. Unique strategies for enhancing photocatalytic performance. Current challenges, concluding remarks and prospective developments in this field.